Managing Educational Quality in Islamic Senior High Schools: Academic Character Integration through Strategic Education Management - Sri Haningsih; Burhan Nudin; Shubhi Mahmashony Harimurti; Nurkhamimi Zainuddin; Moh. Solikul Hadi; Yushfi Nidaul Khoiri Erisyah Putra (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2026)
This study examines how Islamic Senior High Schools (Madrasah Aliyah) in Indonesia manage educational quality by systematically integrating academic achievement and character formation through the Plan-Do-Check-Act (PDCA) cycle within Total Quality Management (TQM) frameworks. Unlike previous research treating character education as supplementary, this study positions it as strategic management. Using a qualitative multiple-case study design, data were collected from three State Islamic Senior High Schools through interviews, observations, focus groups, and document analysis. The study investigated PDCA implementation in each school and patterns across institutional contexts. Findings reveal three management models: (1) structural-regulative (MAN X), emphasizing discipline through strict SOPs; (2) community-collaborative (MAN Y), integrating pesantren culture and parental involvement; and (3) innovation-capacity oriented (MAN Z), cultivating literacy and 21st-century skills. Cross-case analysis shows all schools applied PDCA principles—strategic planning (Plan), consistent implementation (Do), integrated evaluation (Check), and improvement (Act). Educational quality in faith-based schools is enhanced when academic and character dimensions are embedded throughout the management cycle. This research demonstrates how TQM-PDCA frameworks can be contextualized for faith-based schools in developing countries and identifies critical gaps in quality systems that require strengthening.